2015
DOI: 10.1159/000381631
|View full text |Cite
|
Sign up to set email alerts
|

NADIR: A Non-Interventional Study on the Prophylaxis of Chemotherapy-Induced Neutropenia Using Lipegfilgrastim - First Interim Analysis

Abstract: Background: The non-interventional study (NIS) NADIR was designed to assess the effectiveness and safety of lipegfilgrastim, a novel glycopegylated granulocyte-colony stimulating factor, in reducing the risk of both febrile and severe neutropenia. Methods: Here, the interim analysis of NIS Nadir performed under real-world conditions at 80 oncology practices across Germany is reported. For a patient to be included, lipegfilgrastim at a subcutaneous single dose of 6 mg had to be administered during at least 1 cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
(26 reference statements)
1
6
0
Order By: Relevance
“…A real-world study in Belgium and Luxembourg found that patients receiving lipegfilgrastim had a lower incidence of grade 3 and grade 4 neutropenia than did those receiving it secondarily (13). Another prospective, non-interventional, multicenter study conducted in Germany also reported that primarily administration of lipegfilgrastim demonstrated a lower incidence of severe neutropenia compared with secondary administration (14). These findings are in line with our results.…”
Section: Discussionsupporting
confidence: 91%
“…A real-world study in Belgium and Luxembourg found that patients receiving lipegfilgrastim had a lower incidence of grade 3 and grade 4 neutropenia than did those receiving it secondarily (13). Another prospective, non-interventional, multicenter study conducted in Germany also reported that primarily administration of lipegfilgrastim demonstrated a lower incidence of severe neutropenia compared with secondary administration (14). These findings are in line with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, within Protroca, the FN rate was calculated over all CT cycles and not only for the first cycle. In the NIS NADIR that investigated the use of lipegfilgrastim as prophylaxis for cancer patients, FN was only observed in patients receiving secondary prophylaxis and was 2.9 and 7.1% for all cancer and BC patients, respectively [16]. Patients with primary prophylaxis did not exhibit any FN in the first CT cycle of the NADIR study (rate = 0%) in contrast to Protroca, where, in addition, all CT cycles were taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…The interim results were reported previously. 18,19 The primary objective of this NIS was the incidence of chemotherapy-induced severe neutropenia, FN, and neutropeniaassociated complications. Here, we present the final data on patients with NHL including a subgroup of patients treated with the dosedense regimens CHOP-14, R-CHOP-14, or R-CHOEP-14, which are all associated with a high risk of FN.…”
Section: The Non-interventional Study Nadirmentioning
confidence: 99%
“…In 2013, the non‐interventional study (NIS) NADIR was initiated in Germany to evaluate the effectiveness and safety of lipegfilgrastim in patients with different tumor entities under chemotherapy in routine clinical practice. The interim results were reported previously . The primary objective of this NIS was the incidence of chemotherapy‐induced severe neutropenia, FN, and neutropenia‐associated complications.…”
Section: Introductionmentioning
confidence: 99%